PEDAGOGICAL CONDITIONS OF PRACTICAL PREPARATION OF SCHOOL MANAGERS FOR THE IMPLEMENTATION OF QUALITY MANAGEMENT IN EDUCATION - Juraeva, Nargiza (Журнал иностранных языков и лингвистики, 2022)
This article developed a theoretical analysis of the effective implementation of the quality management system of school education, a training module “quality management of school education” for the development of professional competencies of educational managers in terms of the effective implementation of the quality management of school education, and a system of training aimed at implementing the practical readiness of school managers to, the scientific views that theory and practice serve to ensure unity are covered.